The Relationship between giving formula milk and the incidence of diarrhea in babies 0-6 months in the Work Area of Batangtoru Public Health Center in 2023 - Mutia, Fatma; Lubis, Arisa Harfa Said; Harahap, Irawati (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
ABSTRACT Giving formula milk too early will also reduce breast milk consumption, and if it is too late it will cause the baby to be malnourished and feeding at an early age will result in the baby's digestive ability not being ready to accept additional food. The problem of giving formula milk is greatly influenced by the baby's health behavior such as diarrhea. The mother's knowledge about giving formula milk and having a good attitude in giving formula milk can determine the best development for her child. The aim of this research is to determine the relationship between breastfeeding mothers regarding giving formula milk to babies 0-6 months with the incidence of diarrhea in the Batangtoru Community Health Center Work Area in 2023. This type of research is quantitative with a cross sectional approach method. The population in this study were all mothers who had babies aged 0-6 months, totaling 49 mothers. Because the population is less than 50 people, the sampling technique uses a total sampling technique. Chi Square Test results obtained p=0.000 (<0.05). So the conclusion is that there is a relationship between giving formula milk and the incidence of diarrhea in babies 0-6 months in the Batangtoru Health Center Working Area. 21 people were given formula milk, 21 people had diarrhea. It is recommended that the results of this study can provide information to respondents regarding knowledge of giving formula milk to babies 0-6 months with the incidence of diarrhea. Keywords: Formula feeding, incidence of diarrhea, babies 0-6 months